1991
DOI: 10.1007/bf00260706
|View full text |Cite
|
Sign up to set email alerts
|

TheSaccharomyces cerevisiae genes (CMP1 andCMP2) encoding calmodulin-binding proteins homologous to the catalytic subunit of mammalian protein phosphatase 2B

Abstract: Saccharomyces cerevisiae genomic clones that encode calmodulin-binding proteins were isolated by screening a lambda gt11 expression library using 125I-labeled calmodulin as probe. Among the cloned yeast genes, we found two closely related genes (CMP1 and CMP2) that encode proteins homologous to the catalytic subunit of phosphoprotein phosphatase. The presumed CMP1 protein (62,999 Da) and CMP2 protein (68,496 Da) contain a 23 amino acid sequence very similar to those identified as calmodulin-binding sites in ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
117
0
1

Year Published

1992
1992
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(120 citation statements)
references
References 27 publications
2
117
0
1
Order By: Relevance
“…Based on chromosomal blots and low stringency Southern hybridization analyses, we also concluded that there was at least one other CMPI-related gene. In accord with our results, Liu et al (1991) found that disruption of C M P l was not lethal. In addition, they found that disruption of CMP2 was also not lethal in thc presence or absence of a functional C M P l gene.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Based on chromosomal blots and low stringency Southern hybridization analyses, we also concluded that there was at least one other CMPI-related gene. In accord with our results, Liu et al (1991) found that disruption of C M P l was not lethal. In addition, they found that disruption of CMP2 was also not lethal in thc presence or absence of a functional C M P l gene.…”
Section: Discussionsupporting
confidence: 92%
“…This strongly suggests that all these phosphatases have highly conserved functions with great constraints placed on sequence divergence. While the manuscript of this paper was in preparation, another laboratory reported the cloning and sequence of the same yeast gene reported here (Liu et al, 1991). They used I2'I-labeled bovine brain calmodulin to screen a E.gtl1 yeast expression library and identified two sets of overlapping DNA fragments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two yeast genes, homologous to mammalian calcineurin A catalytic subunits, have been identified. They are CNA1 and CNA2, also known as CMP1 and CMP2 [9,10]. Comparison of the amino acid sequences of Cnalp and Cna2p with that of a mammalian calcineurin A subunit reveals a presumptive calmodulin-binding site and an AID sequence in both the polypeptides [9] (Fig.…”
Section: ~-Galactosidase Assay and Induction Of Metallothionein Exmentioning
confidence: 99%
“…In fact, yeast cells possess two genes, CNA1 and CNA2, homologous to the mammalian A subunit [9,10]. Both the Cnal and Cna2 proteins contain regions which have similarity to the putative AID sequence of the mammalian enzyme [9].…”
Section: Introductionmentioning
confidence: 99%